1989
DOI: 10.1111/j.1651-2227.1989.tb11166.x
|View full text |Cite
|
Sign up to set email alerts
|

Soft Neurological Signs and EEG Pattern in Rural Malnourished Children

Abstract: The present study was carried out in 208, 8-10 yr old male, rural, primary school children of Kashi Vidyapith Block, Varanasi. These children were examined for anthropometry, soft neurological signs and electroencephalographic pattern. It was found that the presence of soft neurological signs was related to the severity of malnutrition. The relationship between nutritional status and motor tasks showed that the performance in successive finger tapping, toe tapping, heel toe tapping, hand patting and alternatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
1
9
0
2
Order By: Relevance
“…Our finding that RSCM performance is poorer in stunted children concurs with the findings of other studies that have used tasks from the Neurological Examination of Soft Signs, 7–9 and we controlled more extensively for socioeconomic differences. One study also found differences in performance on Grooved Pegboard tests, 6 but we are unaware of another study with undernourished children using similar pencil and paper tasks.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding that RSCM performance is poorer in stunted children concurs with the findings of other studies that have used tasks from the Neurological Examination of Soft Signs, 7–9 and we controlled more extensively for socioeconomic differences. One study also found differences in performance on Grooved Pegboard tests, 6 but we are unaware of another study with undernourished children using similar pencil and paper tasks.…”
Section: Discussionsupporting
confidence: 89%
“…There is limited evidence that children’s fine motor ability is affected by undernutrition 6,7 . In a study of Indian school‐aged males, low weight for age was associated with poorer performance on motor tasks; out of the 16 males with the worst scores, 15 had abnormal electroencephalogram patterns, mostly in the frontal lobes 8 . In another study, 10‐year‐old Indian children who were underweight and stunted in early childhood had deficits in timed coordinated tasks and balance, 9 but not in dexterity 10 .…”
mentioning
confidence: 99%
“…The most consistent EEG finding, based on the derived measure of percenttotal power, was that low boron intake resulted in a shift toward more activity in the lower frequencies and less activity in the higher, dominant frequencies of the EEG spectrum. This is a particularly important finding, considering that the same effect is often observed in response to nonspecific malnutrition (20,21) and heavy metal toxicity (12,22,23). Increased low-frequency activity is typical of states of reduced behavioral activation (i.e., drowsiness) and mental alertness (24), and has been associated with poorer performance on vigilance and psychomotor tasks (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of an association with measures of malnutrition contrasts with previous studies (Galler et al . 1984, 1987; Agarwal et al . 1989) and is surprising given the evidence for the vulnerability of the brain to early nutritional insults (Winick et al .…”
Section: Discussionmentioning
confidence: 99%